2019
DOI: 10.1096/fj.201801551r
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prebiotic supplementation reduces fatty liver development in offspring through altered microbial and metabolomic profiles in rats

Abstract: A maternal high‐fat/sucrose diet, in the presence of maternal obesity, can program increased susceptibility to obesity and metabolic disease in offspring. In particular, nonalcoholic fatty liver disease risk is associated with poor maternal nutrition and obesity status, which may manifest via alterations in gut microbiota. Here, we report that in a preclinical model of diet‐induced maternal obesity, maternal supplementation of a high‐fat/sucrose diet with the prebiotic oligofructose improves glucose tolerance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 85 publications
1
55
0
Order By: Relevance
“…In our study, maternal OFS intake was associated with significantly lower body weight in their offspring, despite offspring across all groups consuming similar caloric intake. This is comparable to previous work showing that maternal OFS consumption reduced body weight and fat mass in offspring at weaning [54] and attenuated hepatic steatosis in offspring fed a high fat/sucrose diet for 23 weeks [55]. Previous studies have demonstrated that prebiotics improve calcium absorption and increase bone mineral content and density [56][57][58].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, maternal OFS intake was associated with significantly lower body weight in their offspring, despite offspring across all groups consuming similar caloric intake. This is comparable to previous work showing that maternal OFS consumption reduced body weight and fat mass in offspring at weaning [54] and attenuated hepatic steatosis in offspring fed a high fat/sucrose diet for 23 weeks [55]. Previous studies have demonstrated that prebiotics improve calcium absorption and increase bone mineral content and density [56][57][58].…”
Section: Discussionsupporting
confidence: 87%
“…In the steatosis study mentioned above [55], gut microbiota differences in prebiotic versus control offspring were most prominent at 3 weeks of age, diminished by 11 weeks of age and absent by 24 weeks of age [55]. Cox et al also found that after cessation of direct LDP, differences in microbial populations were transient, whereas the effects on various phenotypes such as body weight and obesity risk remained throughout life [25].…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that a balanced, diverse, and nutritious diet is universally recommended to meet nutritional needs to improve maternal and birth outcomes [137,138]; however, little is known whether supplementing with certain classes of nutrients in gestation can be beneficial on DOHaD-related disorders induced by various early-life insults in humans. In the current review, we only restrict to nutritional interventions during pregnancy and/or lactation periods as reprogramming strategies to prevent adult diseases of developmental origins in all sorts of animal models, some of which are listed in Table 2 [33,35,124,139,140,141,142,143,144,145,146,147,148,149,150]. Rats are the most commonly used species for developmental programming research.…”
Section: Nutritional Interventions As Reprogramming Strategiesmentioning
confidence: 99%
“…Dietary fiber, one of the non-essential nutrients, has been used as reprogramming strategies to prevent developmental programming of hypertension [124], hepatic steatosis, and insulin resistance [150]. Maternal supplementation with inulin protected adult rat offspring born to dams fed with high-fructose diet against the developmental programming of hypertension [124].…”
Section: Nutritional Interventions As Reprogramming Strategiesmentioning
confidence: 99%
“…Exercise can influence conditions such as type II diabetes onset and progression at the level of muscle-mediated insulinresistance (Way et al, 2016), as well as aspects of the metabolic syndrome and chronic inflammation associated with obesity, and many other aspects of the condition (Pedersen and Saltin, 2015). Nevertheless, even with obesity, epigenetic modifications can occur and progress over time (Desiderio et al, 2016;Pigeyre et al, 2016;Xu et al, 2016), and such changes may have transgenerational influences in both humans (Bays and Scinta, 2015) and preclinical models (Paul et al, 2019), so treating early obesity rather than long-term chronic obesity with exercise may yield substantially different outcomes for many individuals.…”
mentioning
confidence: 99%